Exploring the relationship between the Gut Microbiota and Ageing: A possible age modulator (2023)
The gut microbiota (GM) has been the subject of intense research in recent years. Therefore, numerous factors affecting its composition have been thoroughly examined, and with them, their function and role in the individual’s systems. The gut microbiota’s taxonomical composition dramatically impacts older adults’ health status. In this regard, it could either extend their life expectancy via the modulation of metabolic processes and the immune system or, in the case of dysbiosis, predispose them to age-related diseases, including bowel inflammatory and musculoskeletal diseases and metabolic and neurological disorders. In general, the microbiome of the elderly tends to present taxonomic and functional changes, which can function as a target to modulate the microbiota and improve the health of this population. The GM of centenarians is unique, with the faculty-promoting metabolic pathways capable of preventing and counteracting the different processes associated with age-related diseases. The molecular mechanisms by which the microbiota can exhibit anti-ageing properties are mainly based on anti-inflammatory and antioxidant actions. This review focuses on analysing the current knowledge of gut microbiota characteristics and modifiers, its relationship with ageing, and the GM-modulating approaches to increase life expectancy.